2007
DOI: 10.1167/iovs.06-1089
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Actin Cytoskeletal Integrity on Matrix Metalloproteinase-2 Activation in Cultured Human Trabecular Meshwork Cells

Abstract: These studies indicate that cytochalasin D- and latrunculin A-induced alteration of actin cytoskeletal integrity in HTM cells is associated with MMP-2 activation, most likely through the upregulation of its activator, MT1-MMP. These data provide a mechanistic connection between actin cytoskeletal organization and MMP-2 activation in TM cells and offer new insights into extracellular matrix remodeling in the aqueous outflow pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 54 publications
3
48
0
Order By: Relevance
“…(Santas et al 2003) A recent study showing effects of cytoskeletal modifying agents on matrix metalloproteinases (MMPs) further adds to the complexity of assigning direct roles for the cells or ECM. (Sanka et al 2007) The various GAG-modifying studies mentioned above suggest a direct ECM contribution to the outflow resistance. The initiation of ECM turnover in the TM, mediated by members of the MMP family, also increases outflow facility.…”
Section: Segmental Flowmentioning
confidence: 99%
“…(Santas et al 2003) A recent study showing effects of cytoskeletal modifying agents on matrix metalloproteinases (MMPs) further adds to the complexity of assigning direct roles for the cells or ECM. (Sanka et al 2007) The various GAG-modifying studies mentioned above suggest a direct ECM contribution to the outflow resistance. The initiation of ECM turnover in the TM, mediated by members of the MMP family, also increases outflow facility.…”
Section: Segmental Flowmentioning
confidence: 99%
“…[33][34][35] In addition, a direct cellular contribution, possibly beyond the ECM turnover involvement, appears to affect the outflow resistance in some manner that is currently only partially understood. 10,[36][37][38][39][40][41][42] A large number of cellular cytoskeletal tension/relaxation studies showing acute and more sustained effects on outflow facility have been reported. Numerous studies where cell-related properties, for example, nitric oxide and eNOS, RhoA GTPase, are associated with direct or indirect cellular effects on outflow, suggest additional complexity.…”
Section: How Could the Iop Homeostatic Process Work?mentioning
confidence: 99%
“…Many cytoskeletal manipulations have dramatic effects on both outflow facility and TM cell behavior. 36,37,39,44 Although most of the cytoskeletal research has not been directly applicable to the IOP homeostatic pressure responses, several studies have shown clear effects that may relate to the IOP homeostatic mechanism. 40,[44][45][46][47] Focal ECM Turnover Initially, it was not fully appreciated that the IOP homeostatic ECM turnover events needed to be highly constrained and very focal.…”
Section: Signal Transduction and Cellular Responses To Stretching/prementioning
confidence: 99%
“…Alternatively, endocannabinoids and lysophospholipids impact cell contractility, while lysophospholipids also impact cell-cell junction assembly. To complicate these relationships, it appears that manipulations that impact cellular components that mediate contractility influence MMP activation in different cell types, including TM cells [133]. Unknown to a large extent, however, is the relative role of receptor subtypes and their location in the conventional tract, the degree of cross-talk between mediators and the relative contribution of each potential mechanism to total outflow resistance.…”
Section: Five-year Viewmentioning
confidence: 99%